2016
DOI: 10.3390/scipharm84040724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fragrances on Human Psychophysiological Activity: With Special Reference to Human Electroencephalographic Response

Abstract: The influence of fragrances such as perfumes and room fresheners on the psychophysiological activities of humans has been known for a long time, and its significance is gradually increasing in the medicinal and cosmetic industries. A fragrance consists of volatile chemicals with a molecular weight of less than 300 Da that humans perceive through the olfactory system. In humans, about 300 active olfactory receptor genes are devoted to detecting thousands of different fragrance molecules through a large family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
153
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(161 citation statements)
references
References 145 publications
(195 reference statements)
0
153
0
8
Order By: Relevance
“…A number of studies are being conducted to evaluate the olfactory stimulation effects on humans in order to understand whether odors can produce functional changes such as relaxation and excitation states in the brain [11]. The effect of odors on brain state can be measured by electroencephalography (EEG) through changes in brain wave activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies are being conducted to evaluate the olfactory stimulation effects on humans in order to understand whether odors can produce functional changes such as relaxation and excitation states in the brain [11]. The effect of odors on brain state can be measured by electroencephalography (EEG) through changes in brain wave activity.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, various odorants produced different EEG activity according to gender. Previous studies have suggested that even isomers of odor molecules (carvone, linalool, and limonene) possess different odor qualities and intensities for humans [11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, numerous products are commercially available with aromatherapy benefits, such as perfumes, personal care products, candles, air fresheners, and detergents. Previous studies have reported that aroma inhalation of essential oils exhibits various positive psychophysiological effects by regulating the central nervous system function . For example, peppermint aroma enhances memory, visual attention, task performance, and alertness, and lavender aroma promotes behavior commitment and interpersonal trust …”
Section: Introductionmentioning
confidence: 99%
“…The most widespread are those non-invasive techniques related to readings of brain activity such as electroencephalogram (EGG), positron emission tomography (PET), magnetic resonance imaging (fMRI) or magnetoencephalography (MEG) that allows to register brain activity during the stimulus. These studies help to correlate emotional states, brain activity tests and behavioral studies such as preferences for stimuli (Herz andSchooler, 2002, Sowndhararajan andKim, 2016). But in addition to these tools, neuromarketing allows the integration of other psychophysiological variables (Cuesta, Martinez-Martinez and Cuesta, 2018).…”
Section: Neuromarketingmentioning
confidence: 99%